ANALISIS PERSEPSI MASYARAKAT TERHADAP PENGGUNAAN APLIKASI BPOM MOBILE SEBAGAI JAMINAN KEPERCAYAAN KONSUMEN - Pratiwi, Amalia; Pradita, Ragilia Dwi; Priageng, Silvana Putri; Sartika, Rika Dewi; Fakhturi, Fakhturi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
E-Government is the utilization of technology to provide services to the public more efficiently. The high phenomenon of illegal products makes consumers worried about the safety of products in circulation. This article discusses BPOM Mobile as one of the innovations of the Indonesian government in ensuring the safety and legality of products consumed in everyday life. This research focuses on assessing whether BPOM Mobile can be trusted by the public to ensure that the products consumed are safe. The method used is a literature study and strengthened by interviews with BPOM Mobile users. The result is that BPOM Mobile has been successfully trusted to ensure that the products used are safe, supported by the strict standardization by BPOM itself in granting legal product permits to be marketed. With features such as scanning the product code, the public can easily check whether the product needed is safe. This application still requires improvement due to complaints from users, it is hoped that more features can respond quickly in order to provide more effective services to the community. Keywords: BPOM Mobile, E-Government, Public Service